2017
DOI: 10.4172/2167-0420.1000367
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Morbidity among Women in Reproductive Age: A Systematic Review and Meta-Analysis

Abstract: Background: Prevention against infection and dysfunction of reproductive organ including sexually transmitted disease is one of the three dimensions of reproductive health. Gynecological morbidities affect women's physical health, sexual function, social role, psychological life and religious life. For accurate estimation of gynecological morbidity, population based data are considered to be gold standard. There are no global wide population studies on gynecological morbidities. In this paper, we aimed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Распространённость пролапса тазовых органов составила 13 %, бесплодия -8 %, инфекций половых путей -38 %, нарушений менструального цикла -28 %. Распространённость общей гинекологической заболеваемости составила 22 % [4].…”
Section: актуальностьunclassified
“…Распространённость пролапса тазовых органов составила 13 %, бесплодия -8 %, инфекций половых путей -38 %, нарушений менструального цикла -28 %. Распространённость общей гинекологической заболеваемости составила 22 % [4].…”
Section: актуальностьunclassified
“…Gynecological morbidities include conditions of the reproductive tract which are not associated with a particular pregnancy, such as reproductive tract infections, cervical cell changes, prolapse, infertility, and related morbidities, including urinary tract infections, but may be related to sexual behavior [ 4 , 5 ]. A systematic review and meta-analysis conducted by Dheresa et al [ 6 ] among women of reproductive age revealed an overall pooled random effect prevalence of gynecological morbidity at 22%. These results indicate that the pooled prevalence of overall gynecological morbidity is high, and the authors have concluded that the effects of high gynecological morbidities cause lower fertility in women of reproductive age around the world, especially in developing nations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis conducted by Dheresa et al [ 6 ] among women of reproductive age revealed an overall pooled random effect prevalence of gynecological morbidity at 22%. These results indicate that the pooled prevalence of overall gynecological morbidity is high, and the authors have concluded that the effects of high gynecological morbidities cause lower fertility in women of reproductive age around the world, especially in developing nations [ 6 ]. Similarly, Rasool et al [ 7 ] documented that, in a population of female inhabitants of the Srinagar district in the Kashmir valley (India), 20.28% reported one or more gynecological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based assessment of reproductive health status including the various gynecological morbidities will serve as an important tool for epidemiological surveillance, health service planning, and policy advocacy. [7]…”
Section: Introductionmentioning
confidence: 99%